2011
DOI: 10.1175/wcas-d-10-05004.1
|View full text |Cite
|
Sign up to set email alerts
|

Why Analyze Mental Models of Local Climate Change? A Case from Southern Mozambique

Abstract: People construct mental models of local climate change based on their observations and experiences of past climate events and changes. These mental models offer critical insight into locally important factors that trigger responses to new climate conditions and can be used to ground-truth regional climate models. In this paper, the authors explore mental models of changes to local climate patterns and climate-associated environmental changes over the past 45 years (1963–2008) in two rural communities in Matutú… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…To elicit cultural knowledge about climate change we employed the cognitive and psychometric methods of free listing, pile sorting, multidimensional scaling (MDS) and cluster analysis [32][33][34][35] with ethnographic data, these methods allow us to visualize the content and structure of cultural knowledge about climate change. Specifically, we had individuals in each community sort terms related to climate change into piles, aggregated those piles, and then used MDS to visualize the relationships between the terms.…”
Section: Eliciting Cultural Knowledge Of Climate Changementioning
confidence: 99%
“…To elicit cultural knowledge about climate change we employed the cognitive and psychometric methods of free listing, pile sorting, multidimensional scaling (MDS) and cluster analysis [32][33][34][35] with ethnographic data, these methods allow us to visualize the content and structure of cultural knowledge about climate change. Specifically, we had individuals in each community sort terms related to climate change into piles, aggregated those piles, and then used MDS to visualize the relationships between the terms.…”
Section: Eliciting Cultural Knowledge Of Climate Changementioning
confidence: 99%
“…We used approaches familiar to cognitive and environmental anthropologists for eliciting shared core knowledge of environmental phenomena (cf. Atran et al 2005;Kempton et al 1995;Paolisso 2002Paolisso , 2007Shaffer and Naiene 2011). More specifically, to elicit cultural knowledge about climate change we used cognitive and psychometric approaches: specifically, free listing, pile sorting, and multidimensional scaling (MDS) (Bernard 2006;Kruskal and Wish 1978;Weller and Romney 1988).…”
Section: Participatory Research Approachmentioning
confidence: 99%
“…A previous study showed that 81 percent of respondents consistently attributed the droughts in this region-especially those post-civil war-to failed rain rituals (Shaffer and Naiene 2011). This widespread emphasis during interviews of the failure of rain rituals, despite the exposure of community members to Western scientific explanations for climate change through school or work with non-governmental organizations, encouraged me to pursue additional questions about local ritual practice and outcomes, reasons for failure, observed alterations to rain rituals, and explanations for these changes to better understand local perceptions of climate vulnerability.…”
Section: Ethnographic Fieldwork In Madjadjane and Gala During 2004 Anmentioning
confidence: 93%
“…Locals appreciate the animals, but weak governmental responses to crop raiding and reduced resource access with no compensation frustrates them as their families suffer from reduced household production. Rising temperatures and shifting rainfall patterns over the district have been observed by local residents and measured at the nearest weather station (Shaffer and Naiene 2011). Residents state these changes have affected household production and livelihood activity through declines in crop and wild fruit production, increased elephant crop raiding, more wildfires, and water insecurity.…”
Section: Study Areamentioning
confidence: 99%